Prediksi Jumlah Penjualan Tahun 2024 Menggunakan Metode Regresi Linier - Ferdinan; Martanto (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
In facing the development of the marketplace, such as Shopee, which is growing rapidly in Indonesia, Micro, Small, and Medium Enterprises (MSMEs) increasingly rely on this platform to boost their sales. However, challenges persist, especially in predicting their uncertain sales. Nevertheless, running a business doesn't solely depend on retrospective analysis. To achieve the desired sales target, one approach that can be taken is predicting sales. By making predictions, MSMEs can reduce the risk of losses and optimize profits. It's important to note that these predictions are projective and can be influenced by external factors. This research provides insights into the effectiveness of the linear regression method in predicting sales on the marketplace platform. The study lays the groundwork for small business owners to adopt more advanced analytical methods in facing the rapidly changing market dynamics. Based on the sales prediction results using the linear regression method with the help of the Python programming language, the sales for the year 2024 are projected to be 11,614 orders, with values for MAE (Mean Absolute Error) at 22.89, MSE (Mean Squared Error) at 9.13, RMSE (Root Mean Squared Error) at 3.02, and R2-Score at 0.91. These values indicate an increase in sales predictions for the year 2024 compared to the previous year.